Ammonia emissions from beef cattle feedyards: a review - Lee, Myeongseong; Auvermann, Brent W.; Tedeschi, Luis O.; Koziel, Jacek A.; Brandani, Carolina B.; Gouvêa, Vinícius N.; Smith, Jason K.; Casey, Kenneth D. (Frontiers in Animal Science, 2025)
This review described the state of the science concerning the generation, measurement, and mitigation of ammonia (NH3) emissions from beef cattle feedyards. NH3 emissions primarily come from urinary urea in cattle manure. In the past, constant emission factors were used to inventory NH3 emissions. Currently, NH3 emission factors estimated by process-based mechanistic models reflecting various factors affecting NH3 emissions in the feedyard environment are available. This review of current literature indicated the average NH3 emissions from a beef cattle feedyard was approximately 119 g/head/day (range 24 to 318 g/head/day), and the average NH3 flux was approximately 58 µg/m2/s (range 2 to 185 µg/m2/s). Although more realistic estimates of NH3 emission flux from open-lot livestock facilities were being obtained using process-based models, there was still significant variation depending on the diet composition, manure management practices, and the feedyard environment, including both seasonal weather patterns and synoptic weather events. We note the need to improve inventories of NH3 emissions into categories of crude protein percentage, manure management implemented, and feedyard environment. Some mitigation strategies can be effective, such as diet manipulation, growth-promoting technologies, and manure or pen-surface amendments. Of those, precision diet feeding to meet but not exceed protein requirements appeared to be the most practical way to reduce ammonia emissions over the animals’ feeding period; laboratory studies suggested that shorter-term reductions in emission flux may be possible with the other approaches, but they were far more speculative at this point as to both their efficacy and their cost of implementation.